a, Ta có : \(\left(2x-5\right)\left(x+2\right)\left(3x^2-7\right)=0\)
=> \(\left[{}\begin{matrix}2x-5=0\\x+2=0\\3x^2-7=0\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=\frac{5}{2}\\x=-2\\x=\pm\sqrt{\frac{7}{3}}\end{matrix}\right.\)
Vậy phương trình có nghiệm là \(S=\left\{\frac{5}{2};-2,\sqrt{\frac{7}{3}};-\sqrt{\frac{7}{3}}\right\}\)
b, Ta có : \(\left(x-7\right)\left(x-2\right)=0\)
=> \(\left[{}\begin{matrix}x=7\\x=2\end{matrix}\right.\)
Vậy phương trình có tập nghiệm là \(S=\left\{7;2\right\}\)
a, Ta có : (2x−5)(x+2)(3x2−7)=0(2x−5)(x+2)(3x2−7)=0
=> ⎡⎢⎣2x−5=0x+2=03x2−7=0[2x−5=0x+2=03x2−7=0
=> ⎡⎢ ⎢ ⎢⎣x=52x=−2x=±√73[x=52x=−2x=±73
Vậy phương trình có nghiệm là S={52;−2,√73;−√73}S={52;−2,73;−73}
b, Ta có : (x−7)(x−2)=0(x−7)(x−2)=0
=> [x=7x=2[x=7x=2
Vậy phương trình có tập nghiệm là S={7;2}